ANALISIS PENDAPATAN INDUSTRI RUMAH TANGGA KERIPIK DI KOTA TARAKAN - Oktaviani; Setiawan, Rusdy; Irawati HM; Hatta, Djuanda; Suryaningsih; Masniah, Andi (JURNAL EKONOMI PEMBANGUNAN, 2024)
This research aimed to determine the income of the household scale chips industry in Tarakan City. The data analysis technique uses business income analysis using a quantitative approach. The results of the business income analysis calculation show that the calculated income for Qobidh chips is IDR 44,183,200, Narlam chips IDR 31,881,000 Indri chips IDR 56,333,167 and 3 Dara chips IDR 61,401,500. Using business analysis calculations, namely B/C, the ratio of Qobidh chips is 1.58, Narlam chips 1.27, Indri chips 1.66, and 3 Dara chips 2.33. For the Break Event Point calculation, Qobidh chips are BEP unit 1,112.67/pouch and BEP price Rp9.658,61, Narlam chips are BEP unit 1.250,59/pouch and BEP price Rp.8.794,02, Indri chips are BEP unit I .356,67 /pouch and BEP price Rp9.395,24, and chips 3 Dara BEP unit 1,063.94/pouch and BEP price Rp7.556,39. The payback period calculation results for Qobidh chips are 3.83 years, Narlam chips 1.24 years, Indri chips 1.07 years, and 3 Dara chips 1.68 years